2016
DOI: 10.1155/2016/3803647
|View full text |Cite
|
Sign up to set email alerts
|

Does Tumor Size Influence the Diagnostic Accuracy of Ultrasound-Guided Fine-Needle Aspiration Cytology for Thyroid Nodules?

Abstract: Background. Fine-needle aspiration cytology (FNAC) is diagnostic standard for thyroid nodules. However, the influence of size on FNAC accuracy remains unclear especially in too small or too large thyroid nodules. The objective of this retrospective cohort study was to investigate the effect of nodule size on FNAC accuracy. Methods. All consecutive patients who underwent thyroidectomy for nodules in 2010 were enrolled. FNAC results (according to the Bethesda system) were compared to pathological diagnosis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 24 publications
8
35
3
Order By: Relevance
“…Authors concluded that the large nodule size should not be accepted as an indication for surgery alone. Our results were consistent with studies which suggested decreased sensitivity and increased false‐negative rate of FNAC in large nodules . The present study supports that the cancerous focus may be missed during the FNAC procedure in large nodules despite multiple aspirations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Authors concluded that the large nodule size should not be accepted as an indication for surgery alone. Our results were consistent with studies which suggested decreased sensitivity and increased false‐negative rate of FNAC in large nodules . The present study supports that the cancerous focus may be missed during the FNAC procedure in large nodules despite multiple aspirations.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, Pinchot et al reported that the predictive value of FNAC was lower for the nodules greater than 40 mm and recommended diagnostic surgery for large thyroid nodules . In a recent study, Koo et al observed that the sensitivity of FNAC was lower in nodules greater than 40 mm when compared to smaller ones, whereas specificity was high in all groups of nodule size . Authors suggested that intensive follow‐up and repeat biopsies should be considered for large nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many conflicting reports in terms of false negative rate and nodule size in overall thyroid nodules . Although the reason for the conflicting results among the studies is not clear, it may be related to the proportion of FTC among malignant tumors and the size distribution of PTC in the study population.…”
Section: Discussionmentioning
confidence: 95%
“…Whether the high false negative rate in large thyroid nodules is real is still a matter of controversy; several studies have reported that large nodules were not associated with an increased risk of false negative FNA results . However, other studies have demonstrated that large thyroid nodules showed higher false negative rate than small nodules and that large nodules with benign cytology carry a higher risk of malignancy …”
Section: Introductionmentioning
confidence: 99%